Pendekatan Fungsional di Dalam Penerjemahan - Masduki Masduki (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2013)
Functional approach as one of the approaches in translation has given new colouring in the translation development and research. In translating, translator should not be restrained by source text anymore but be controlled by the function of target text to achieve. In this article, the writer highlights the functional approach and its range, namely: translation as intercultural communication, translation as cultural transfer, and skopos theory.